The Hardiness Personality and Social Support of Subordinates as Determinants of the Leadership Behavior Orientation of the Principal of the 'Aisyiyah Early Childhood Education School in Gresik Regency - Idha Rahayuningsih (Proceedings of International Conference on Psychological Studies (ICPSYCHE), 2022)
The purpose of the study was to prove the influence of personality hardiness and social support of subordinates on the orientation of lleadership behavior at the Principal of the Early Childhood Education School 'Aisyiyah in Gresik, East Java. The correlational quantitative method was used in this study. The research population is the Principal of Kindergarten and Playgroup 'Aisyiyah in Gresik Regency totaling 87 people. A total of 71 people are willing to be research respondents. All participants were female, aged over 25 to 55 years. Data collection techniques for the three variables were carried out by surveying using a questionnaire. Yulk's (1999) leadership behavior orientation scale has three types of orientation, namely task, with 5 items; relationship with 6 items and changes with 6 items. Hardiness scale with 5 items Bartone (1995); and the social support scale of subordinates refers to Sarafino with 10 items. All items have a loading factor greater than 0.6. Conbach's alpha coefficient of each measuring instrument is greater than 0.8. Data processing with SmartPLS student version 3 for measurement model analysis, fit model analysis and structural model analysis. The results of the study prove that the hardiness personality and social support of followers partially affect leadership behavior on task orientation, relationship orientation and change orientation. The results also prove that the hardiness personality and social support of subordinates simultaneously affect task orientation leadership behavior, orientation relationship and orientation change.